2022
DOI: 10.1186/s12886-022-02348-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of virus-related uveitic secondary glaucoma: focus on cytomegalovirus and varicella zoster virus

Abstract: Background We aimed to analyze the clinical characteristics of secondary glaucoma related to cytomegalovirus (CMV)- and varicella zoster virus (VZV)-positive uveitis. Methods In this retrospective study, we enrolled patients with anterior uveitic secondary glaucoma. All the patients underwent aqueous and serum analyses for viral antibody through enzyme-linked immunosorbent assay. Among the 60 included patients, 22 had CMV-negative Posner-Schlossman… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Moreover, iris stromal thickness close to the pupillary edge (M500 and M1000) was found to be significantly and positively associated with corneal endothelium density in PSS-affected eyes, indicating that iris stromal thickness close to the pupillary edge might be a clinical predictor of corneal endothelium density loss in PSS. A previous study has reported that in PSS-affected eyes, the higher prevalence of iris changes was always accompanied by the more serious corneal endothelium loss [ 20 ], which was consistent with our study results. Iris stroma was susceptible to CMV [ 21 ] and could be a reservoir for the latency of CMV [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, iris stromal thickness close to the pupillary edge (M500 and M1000) was found to be significantly and positively associated with corneal endothelium density in PSS-affected eyes, indicating that iris stromal thickness close to the pupillary edge might be a clinical predictor of corneal endothelium density loss in PSS. A previous study has reported that in PSS-affected eyes, the higher prevalence of iris changes was always accompanied by the more serious corneal endothelium loss [ 20 ], which was consistent with our study results. Iris stroma was susceptible to CMV [ 21 ] and could be a reservoir for the latency of CMV [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Morphological observations of iris in PSS by slit lamp microscopy have been reported previously [ 13 , 14 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, no study has measured the iris dimensions in PSS quantitatively for now.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…A plethora of recent research has indicated the involvement of microbes of extra-ocular origin in the development and prognosis of ophthalmic pathologies ( Table 1 ), which include bacteria, fungi, and viruses. It is noteworthy that more recent studies have identified the association of viral components in eye diseases such as uveitis in chronic infections of hepatitis B and hepatitis C viruses [ 30 , 31 ], cytomegalovirus in AMD [ 32 , 33 ], and glaucoma [ 34 ], and more interestingly, coronavirus (COVID-19) is also implicated in ocular diseases [ 35 , 36 , 37 , 38 ]. Several studies have determined that homeostasis of the ocular surface is directly or indirectly impacted by the complex intestinal microbiome [ 39 ].…”
Section: Ocular Microbiomementioning
confidence: 99%